Effect of Blade Design on Angular Velocity of Vertical Axis Wind Turbine – CFD Analysis (Journal of Informatics and Mathematical Sciences, 2018)
Application of Vertical Axis Wind Turbine (VAWT) for generation of power is gaining momentum. However no research has been done to increase the efficiency of blade design for bidirectional wind flow. In the present study the effect of blade profile and thickness for a Savonius wind turbine has been studied. Different blade profiles with thickness 2mm, 4mm and 6mm were modelled. A numerical analysis was done for a bi-directional wind input. The model for the rotor was designed on Solidworks 2017 and a numerical analysis was carried outon commercial CFD software, Ansys Fluent. From the analysis, the angular velocity graphs were plotted with respect to time and compared. The effect of the blade profiles and thickness were studied. And it was observed that 2mm blade with curved profile was most suitable for bidirectional wind flow as it gains stable velocity sooner which is an important factor for power generation.
Keywords: Vertical axis wind turbine; Blade design; Numerical analysis; Angular velocity; Bidirectional wind flow